The Effect of Intrathecal Fentanyl on Bispectral Index during Spinal Anesthesia in Patients with Lower Limb Orthopedic Surgery - Shahryar Sane (Journal of Global Pharma Technology, 2017)
Objective The addition of opioids to local anesthetics in spinal anesthesia modulates some aspects of anesthesia and analgesia. Accordingly, this study sought to evaluate the effect of adding intrathecal fentanyl on bispectral index (BIS) during spinal anesthesia. Materials and Methods According to prospective clinical trial studies, the patients undergoing lower limb orthopedic surgery were randomly divided into 2 groups. Group 1 received 12.5 mg of 0.5% hyperbaric bupivacaine (HBB), while Group 2 received 12.5 mg of HBB plus 20 µg of intrathecal fentanyl. After the induction of spinal anesthesia, a bispectral index (BIS) monitor was connected and baseline values were recorded for each patient. BIS, vital signs, nausea and vomiting and shivering were recorded for each group. Results A total of 54 subjects participated in the study and underwent analysis. The recorded BIS was different between the two groups at all the time points. At all the times, BIS values were lower in the fentanyl group compared to those in the other group. After spinal anesthesia, the changing trend of BIS reduced until the 45th minute for fentanyl group. In 30th and 45th minute after spinal anesthesia, BIS had the highest reduction in fentanyl group (P= 0.01).Conclusions Although the BIS scores began to decrease during spinal anesthesia using hyperbaric bupivacaine alone or with intrathecal fentanyl, the greatest reduction from baseline BIS values occurred adding intrathecal fentanyl. Moreover, maximum reductions of BIS scores appeared at 30 and 45minutes after the induction of spinal anesthesia.Keywords: Spinal anesthesia, Bispectral index, Fentanyl, Bupivacaine.